FRI0617-HPR What are the Educational Needs of Nurses Involved in the Care of Childen and Young People with Rheumatic Disease?. (9th June 2015) - Smith, N.; Foster, H.; Wyllie, R.; English, C.; Davies, B.; Rapley, T.
Abstract : Background: Recent advances in the management of paediatric and adolescent rheumatology have developed the need for highly specialist nurses within the multidisciplinary team. This has resulted in nurses working in shared care within other health care settings (e.g. community care, primary care, general paediatrics and adult rheumatology) demanding an enhanced knowledge base and new skill set. There is an important role for education and support for not only nurse specialists but also nursing colleagues. Objectives: This study aims to establish the essential "core" learning needs of nurses delivering care to children and young people with rheumatic disease within a variety of health care settings. Methods: Multi-method research was conducted using online survey, focus groups and interviews with key nursing stakeholder groups including clinical nurse specialists (CNS, n=28), nursing students (n=15), health visitors (n=3) and nurses from general paediatrics (n=2), community (n=7), research (n=5) and adult rheumatology (n=4). An online survey of CNS within the British Society for Paediatric and Adolescent Rheumatology (BSPAR) (response rate: 77%, with 27/35 respondents) ascertained expert opinion about educational needs based on experience, knowledge and skills, and how these mapped to the needs of different nursing groups. The survey results informed the questions for focus groups and 1-1 interviews, which were recorded and transcribed to further explore the educational needs of nurses working outside of the specialism. Transcripts were analysed qualitatively using thematic analysis. This study had ethical approval with informed consent from all participants. Results: Four core themes emerged: (1) Need for Increased Awareness about Rheumatic Disease, (2) Impact of Personal Experience and Nursing Role, (3) Need for Increased Knowledge about Rheumatic Disease and Management, and (4) Design Components for an Impactful Learning and Information Resource. The level of knowledge needed was stratified by what would be expected within the different nursing roles. The key topics include understanding of conditions and how they may present, treatment and medications, impact of disease and treatment on the child/young person and family, available support for themselves as health care providers, and access to resources to support patients and families, along with contemporary information and research to enable them to be well informed. Conclusions: This study has identified "core" learning needs for all nursing groups. These learning needs appear dependent on past experience and what would be expected within the spectrum of nursing roles, and the level of knowledge required ranged from novice to expert. Future work will develop resources to meet these educational requirements. Disclosure of Interest: None declared